ISSUES OF THE COMPLETENESS OF THE SUBJECT OF CIRCUMSTANCES IN PROOF IN THE THEORY AND PRACTICE OF THE CRIMINAL PROCEDURE - D. N. Rogozhkin (Russian Journal of Economics and Law)
Objective: To ground the necessity of enlarging the lists of circumstances subject to proving, stipulated in Art. 73 of the Russian Criminal-Procedural Code. Methods: general dialectic method of cognition, allowing to study the phenomena and processes of ambient reality in their historical development, interconnection and interdependence, and general scientific, special and private legal research methods based on it. Results: Basing on the carried out analysis of the subject of circumstance in proof in criminal court procedure, it is stated that the list of circumstances subject to proving, stipulated in Art. 73 of the Russian Criminal-Procedural Code, needs enlarging by adding such circumstances as amnesty and oblivion, and the list of circumstances subject to establishment (part 2 art. 73 of the Russian Criminal-Procedural Code), besides circumstances facilitating the crime committing, should contain the circumstances stipulated in Art. 27 of the Russian Criminal-Procedural Code “Bases for termination of prosecution” and Art. 413 of the Russian Criminal-Procedural Code “Bases for resuming a criminal case procedure due to the new or newly revealed circumstances”. Scientific novelty: For the first time the necessity is grounded to include into the list of circumstances subject to establishment (part 2 art. 73 of the Russian Criminal-Procedural Code), the circumstances which can serve as bases for termination of prosecution (Art. 27 of the Russian Criminal-Procedural Code), and circumstances possessing the features of the new or newly revealed circumstance sigа также serving as the basis for resuming a criminal case procedure (Art. 413 of the Russian Criminal-Procedural Code). Practical value: The theoretical provisions formulated in the research allow to ensure the planed and purposeful character of proving procedure in criminal cases. The research results increase the actual knowledge about the circumstances in proof, ensure the similarity of researchers’ positions in scientific discussion. Besides, the ideas expressed in the article can be used in the educational process of higher professional education establishments of juridical sphere, and in up-grading qualification of practical staff and scientific-academic personnel in the sphere of jurisprudence.